Retraction: Transition-metal-free synthesis of conjugated microporous polymers via amine-catalyzed Suzuki–Miyaura coupling reaction. Issue 47 (30th November 2021) - Liu, Qingmin; Jin, Shangbin; Tan, Bien
Abstract : Retraction of 'Transition-metal-free synthesis of conjugated microporous polymers via amine-catalyzed Suzuki–Miyaura coupling reaction' by Qingmin Liu et al., Chem. Sci., 2021, DOI: ; 10.1039/d1sc03970a .